Neural and behavioral investigations into timbre perception - Town, Stephen M.; Bizley, Jennifer K. (Frontiers in Systems Neuroscience, 2013)
Timbre is the attribute that distinguishes sounds of equal pitch, loudness and duration. It contributes to our perception and discrimination of different vowels and consonants in speech, instruments in music and environmental sounds. Here we begin by reviewing human timbre perception and the spectral and temporal acoustic features that give rise to timbre in speech, musical and environmental sounds. We also consider the perception of timbre by animals, both in the case of human vowels and non-human vocalizations. We then explore the neural representation of timbre, first within the peripheral auditory system and later at the level of the auditory cortex. We examine the neural networks that are implicated in timbre perception and the computations that may be performed in auditory cortex to enable listeners to extract information about timbre. We consider whether single neurons in auditory cortex are capable of representing spectral timbre independently of changes in other perceptual attributes and the mechanisms that may shape neural sensitivity to timbre. Finally, we conclude by outlining some of the questions that remain about the role of neural mechanisms in behavior and consider some potentially fruitful avenues for future research.